Effect of Liraglutide on Cardiometabolic Risk Profile in People with Coronary Artery Disease with or without Type 2 Diabetes: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Nowrouzi-Sohrabi, Peyman; Soroush, Negin; Tabrizi, Reza; Shabani-Borujeni, Mojtaba; Rezaei, Shahla; Jafari, Fatemeh; Hosseini-Bensenjan, Mahnaz; Stricker, Bruno H.; van Hoek, Mandy; Ahmadizar, Fariba (Frontiers in Pharmacology, 2021)
Background: The relative advantage of liraglutide in a various subset of patients remains unclear. We conducted a systematic review and meta-analysis on randomized clinical trials (RCTs) to determine the effects of liraglutide compared to placebo on cardiometabolic profile in elderly patients with established coronary artery disease (CAD) with or without type 2 diabetes mellitus (T2D). Methods: Online database searches were conducted in PubMed, Scopus, EMBASE, Web of Science, Cochrane library, and Google Scholar from incept up to 20th December 2019 to identify RCTs assessing the effects of liraglutide supplementation on cardiometabolic profile. We used the random- or fixed-effect models to pool the weighted mean differences (WMDs) and 95% confidence intervals (CIs). Results: Out of a total of 6773 citations, 6 articles (9 RCTs) with 294 patients (mean age, 61.21 years; 19% women) were included. Our findings presented as WMD and 95%CI showed a statistical significant decrease in hemoglobin A1c (HbA1c) [-0.32 %; -0.41; -0.22, P< 0.001; I2= 0.0% (with 8 RCTs)], body mass index (BMI) [-0.94 kg/m2; -1.27; - 0.60, P< 0.001; I2= 0.0% (with 7 RCTs)], and waist circumference [-2.63 cm; -3.63; - 1.63, P< 0.001; I2= 0.0% (with 3 RCTs)]. Through a set of subgroup analyses, we found a significant reduction in BMI in CAD patients with T2D [WMD =-1.06; 95% CI, -1.42, -0.70, P<0.001; I2= 0.0% (with 4 RCTs)] compared to CAD only patients [WMD =0.02; 95% CI, -0.97, 1.01, P=0.96; I2= 0.0% (with 3 RCTs)]. In a sensitivity analysis, we also observed a significant increase in heart rate [3.30 bpm; 0.71; 5.88, P= 0.012; I2= 39.4% (with 6 RCTs)], albeit not statistically significant, in the liraglutide group compared with the placebo group. No significant changes in blood pressure, and lipid profiles were observed. Conclusion: Among elderly patients with established CAD, liraglutide significantly improved HbA1c, BMI, and waist circumference values, where the effect on BMI was more robust in patients with T2D compared to those without.